Income and food Engel curves in Rwanda: A household microdata analysis - Aimable Nsabimana; Ranjula Bali Swain; Yves Surry; Jean Chrysostome Ngabitsinze (Agricultural and Food Economics, 2020)
Food insecurity and malnutrition are still major challenges for large proportions of households in Sub-Saharan Africa. The empirical literature on food demand, however, suggests mixed evidence on the roles of income and other socio-economic attributes on food demand. This study analyzes the food demand among households in Rwanda, based on nationally representative household expenditures and demographic (EICV4, 2013/14) survey data. The results show that poor households consume merely food containing higher carbohydrates and starches. Further, the study finds that the majority of rural households spend almost nothing on micronutrients from animal products, suggesting that effective targeted food policy interventions for poor and rural households may play an important role in reducing the incidence of malnutrition through improving food diets.
Keywords: 330; Food Engel curve; Household food demand; Rwanda; Sub-Sahara Africa